Singular Vector For A Shallow Water Model - Dussadee Sukawat, Chularat Srikul (IIUM Engineering Journal, 2012)
The atmosphere is a chaotic dynamical system, small errors in the initial condition of an atmospheric model can lead to growing errors in the forecast. In order to reduce uncertainty in the forecast which occur from using only one initial condition from many possible initial conditions, more initial conditions are required. In practice, however, there is only single observation available for the initial condition. In this paper the singular vector has been applied to a single level shallow water model of the atmosphere to generate more initial conditions from one observation. ABSTRAK: Atmosfera ialah satu sistem dinamik yang huru-hara. Kesilapan kecil dalam kondisi awal model atmosfera boleh membawa kepada kesilapan yang semakin meningkat di dalam ramalan. Dalam usaha untuk mengurangkan ketidakpastian dalam ramalan yang berlaku dari menggunakan hanya satu kondisi awal, lebih banyak kondisi awal diperlukan. Secara praktikalnya, walau bagaimanapun, hanya terdapat satu pemerhatian yang sedia ada untuk kondisi awal. Kajian ini menerangkan vektor tunggal telah digunakan untuk model air cetek tahap atmosfera untuk menghasilkan lebih banyak kondisi awal dari satu pemerhatian. KEYWORDS: shallow water model; tangent linear model; adjoint linear model; singular vector